Comparison of self-myofascial release and stretching exercises in individuals with piriformis syndrome: A randomised controlled trial - Ergezen, Gizem; Şahin, Mustafa (MA Healthcare Ltd, 2023)
Background/Aims Piriformis syndrome is a condition caused by compression of the sciatic nerve, causing pain, tingling and numbness. Although conservative treatment includes hip muscle strengthening and stretching, there is no proven treatment method in the literature. This study was conducted to investigate the effect of stretching and myofascial releasing methods added to traditional physiotherapy in piriformis syndrome. Methods This prospective, randomised controlled study was completed with 63 individuals between the ages of 20 and 40 years. Participants were randomised into three groups: piriformis muscle stretch group (n=22), self-myofascial release group (n=21) and control group (n=20). All participants were enrolled in a 4-week muscle strengthening home exercise programme. In addition, the two intervention groups performed stretching and self-myofascial relaxation exercises respectively. The primary outcome was pain intensity and the secondary outcome was the range of motion of the hip. Results After 4 weeks of exercises, the level of pain intensity felt in the hip decreased significantly and hip joint range of motion increased significantly in all three groups (P[removed]
Keywords: Myofascial Release; Passive Stretching; Piriformis Syndrome